Effect of social network use and advertising on anthropometric status and dietary intake: Social network, advertising and dietary intake - Erdem, Nihal Zekiye; Tarakçı , Nadide Gizem; Bayraktaroğlu , Emre (Progress in Nutrition, 2022)
Objective: The aim of this study was to examine the effects of social media use and advertisements on anthropometric status and nutrition in adults. In this randomized and cross-sectional study, 9918 adults aged between 18 and 65 years in 30 cities of Turkey were included. Method: Within the scope of the research, a questionnaire consisting of 40 questions in 4 sections was applied to the participants. The questions asked included socio-demographic information, anthropometric measurements, reliance on information about nutrition in social media and advertisements, changes in eating habits caused by social media and advertisements, information about nutrition, and 24-hour food consumption frequency. Results: People who use Instagram, books, and Pinterest have been found to have lower body weight, BMI, and carbohydrate, fat, and cholesterol intake. People who use Instagram, books, and Pinterest have been found to have lower body weight, BMI, and carbohydrate, fat, and cholesterol intake. It has been observed that individuals who modified their eating habits after being persuaded by media coverage of nutrition issues had considerably lower weights, BMIs, and energy, protein, fat, and cholesterol intakes, while having higher fiber intake. It has been revealed that celebrities in commercials or social media advertising have no bearing on consumer decisions to buy products. Instead, consumers pay attention to cited sources in social media posts that discuss nutrition-related topics and seek out dietary advice from dietitians. Conclusion: It has been determined that social media and advertisements, fast and effective means of obtaining information, affect eating habits, purchasing behaviors, body compositions and health status of individuals. Hence, only dietitians should share on nutrition through social media and advertisements bearing ethical rules in mind and necessary inspections should be carried out by relevant institutions.